La scrittura è un duello: Dialoghetto del vespro - Lanera, Licia; Spagnulo, Riccardo (Mimesis Journal, 2014)
It is a dialogue among the two leading artists of Fibre Parallele, a dialogue that could be happened at different moments, but it is here fictitiously condensed in a single unit of time. This is a dialogue that goes through the stages of the creation of the dramaturgy of Fibre Parralelle’s performances. This is a dialogue that should be read aloud.